Effect of Using Spot the Dictogloss to Students’ Listening Skill - Sabilla Sari Faradini; Sri Sugiharti; Eka Wilany (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
This research was aimed to find out whether significant effect of using Spot the Dictogloss to students’ listening skill at second grade students of SMAN 17 Batam in academic years 2015/2016. The research conducted experimental research in April 2016 and was held on second grade with the number of sample was 60 students of SMAN 17 Batam. The writer used cluster random sampling technique to determine class of the research. In this research, the writer conducted in two classes, XI IIS 1 and XI IIS. The experimental class was taught listening by using spot the dictogloss, whereas the control class was taught listening by using running dictation strategy. Data was collected by multiple choice test. The result of the research showed there was a significant difference of the students’ achievement before conducted treatment which they had mean 40.5 for experimental class and 42.5 for control class. The average of the students’ achievement after conducted treatment in experimental class was 55.33 and in control class was 48.33. Based on this finding, it is suggested that spot the dictogloss could be used by the teacher to improve students’ listening skill.Keywords: spot the dictogloss, listening skill